Opportunities to diagnose fibrotic lung diseases in routine care: A primary care cohort study. Issue 12 (11th May 2020) - Jones, Mark G.; Hillyar, Christopher R.T.; Nibber, Anjan; Chisholm, Alison; Wilson, Andrew; Maher, Toby M.; Kaplan, Alan; Price, David; Walsh, Simon; Richeldi, Luca; ,
ABSTRACT: Background and objective: Temporal trends of healthcare use in the period before a diagnosis of pulmonary fibrosis are poorly understood. We investigated trends in respiratory symptoms and LR HRU in the 10 years prior to diagnosis. Methods: We analysed a primary care clinical cohort database (UK OPCRD) and assessed patients aged ≥40 years who had an electronically coded diagnosis of pulmonary fibrosis between 2005 and 2015 and a minimum 2 years of continuous medical records prior to diagnosis. Exclusion criteria consisted of electronic codes for recognized causes of pulmonary fibrosis such as CTD, sarcoidosis or EAA. Results: Data for 2223 patients were assessed. Over the 10 years prior to diagnosis of pulmonary fibrosis, there was a progressive increase in HRU across multiple LR‐related domains. Five years before diagnosis, 18% of patients had multiple healthcare contacts for LR complaints; this increased to 79% in the year before diagnosis, with 38% of patients having five or more healthcare contacts. Conclusion: There are opportunities to diagnose pulmonary fibrosis at an earlier stage; research into case‐finding algorithms and strategies to educate primary care physicians is required. Abstract : We analysed a primary care clinical cohort database to investigate respiratory symptoms and healthcare use in the 10 years prior to a diagnosis of pulmonary fibrosis. Utilization progressively increased in the years prior to diagnosis, suggesting multiple opportunities for diagnosis at an earlier stage. See related Editorial